AKULTURASI BUDAYA PADA MASJID JAMI’ SHIRATAL MUSTAQIEM SEBAGAI OBJEK DESTINASI WISATA RELIGI DI SAMARINDA - Nur Husniah Thamrin; Hatta Musthafa Adham Putra (Jurnal Arsitektur ARCADE, 2020)
In its development of mosque architecture, various forms and styles of mosque buildings emerged throughout the Islamic world, including Indonesia. The shape is diverse, depending on various factors, including geographical conditions, local culture, mixing culture and technology. Thus the building of the Islamic world mosque shows its own image due to the different climate, building materials, technology, or expertise of artists. The Jami ’Shirathal Mustaqiem Mosque is one of the oldest religious buildings now incorporated by the East Kalimantan cultural heritage body as a religious tourism object in Samarinda.Based on the results of preliminary observations on the Shirathal Mustaqim mosque building, there are seen a number of cultural blends both from interior ornaments and facade elements.This mixing of cultures forms a harmony that contains aesthetic values. The research was limited only to interior ornaments and facade elements namely the shape of the mosque, and ornaments on the roof. The method used is a qualitative method with regard to conditions on the object, conformity to the theory and data available in the field. The results of this study are the influence of external forces on local culture, in this case the culture of the people of East Kalimantan, namely the culture of Kutai and foreign cultures such as Java, as well as foreign cultures such as the Netherlands.